Assessing the reliability of laboratory test procedures for predicting concrete field performance against alkali-aggregate reaction (AAR) - Ana Bergmann; Leandro F.M. Sanchez (Cement)
Alkali aggregate reaction (AAR) affected structures show reduced serviceability and premature distress in over 50 countries worldwide. Several laboratory test protocols have been proposed to evaluate the potential reactivity of aggregates by varying the conditions known to trigger and sustain the reaction. Among them, the most popular methods are the accelerated mortar bar test (AMBT) and the concrete prism test (CPT). Nevertheless, exposure site data, displaying the behaviour of concrete blocks exposed to real environmental conditions, has increased considerably recently, showing significant discrepancies between laboratory and concrete field performance. This study explores the reliability of laboratory tests, indicating moderate accuracy in predicting field performance for the AMBT and the CPT. The findings highlight an opportunity for recalibration of these methods through advanced analytical models that account for environmental conditions, alkali content, and the presence of SCMs to improve predictive accuracy. These measures will enhance concrete infrastructure safety by identifying risks associated with incorporating AAR-prone aggregates into new structures.